1997
DOI: 10.1103/physrevlett.79.3202
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Properties of Fracture Precursors

Abstract: We present the data of a mode-I fracture experiment. The samples are broken under imposed pressure. The acoustic emission of microfractures before the breakup of the sample is registered. From the acoustic signals, the position of microfractures and the energy released are calculated. A measure of the clustering of microfractures yields information about the critical load. The statistics from energy measurements strongly suggest that the fracture can be viewed as a critical phenomenon; energy events are distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

29
239
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(272 citation statements)
references
References 20 publications
29
239
1
1
Order By: Relevance
“…The presence of log-periodic correction to scaling in the elastic energy released has also been demonstrated numerically for the thermal fuse model [35,24] using a novel averaging procedure, called the "canonical ensemble averaging". A recent experimental study of rupture of fiber-glass composites has also confirmed the critical scenario [36].These results indicate that the "critical" behavior is not restricted to limited stress amplification but may well pertain to a much broader class of systems. This needs to be investigated more.…”
supporting
confidence: 50%
“…The presence of log-periodic correction to scaling in the elastic energy released has also been demonstrated numerically for the thermal fuse model [35,24] using a novel averaging procedure, called the "canonical ensemble averaging". A recent experimental study of rupture of fiber-glass composites has also confirmed the critical scenario [36].These results indicate that the "critical" behavior is not restricted to limited stress amplification but may well pertain to a much broader class of systems. This needs to be investigated more.…”
supporting
confidence: 50%
“…Experimental observations have been reported for several materials such as wood [12], cellular glass [13], concrete [14] and paper [15], but universality in the scaling exponents does not appear to be present.…”
Section: Introductionmentioning
confidence: 99%
“…The cluster growth near the critical time also exhibits spatial scaling in addition to the temporal scaling, namely as fracture develops with time, the connectivity length of the clusters increases and diverges at t c . Recent experiments on the rupture of fiber-glass composites have also confirmed the critical scenario [19]. Johansen and Sornette [20] have recently re-analyzed the acoustic emissions recorded during the pressurization of spherical tanks of kevlar or carbon fibers impregnated in a resin matrix wrapped up around a thin metallic liner (steel or titanium) fabricated and instrumented by Aerospatiale-Matra Inc.…”
Section: Introductionmentioning
confidence: 99%
“…As we said above, the critical rupture concept establishes theoretically this law (1) as the result of the cooperative organization of precursory damage preparing the global rupture. If an observable such as the rate of acoustic emissions radiated during loading exhibit an acceleration close to rupture of the form (1) as documented in several experiments [15,19,20], it is clear that one can try to fit the data by (1) and get a prediction from the determination of t c .…”
Section: Introductionmentioning
confidence: 99%